Salts of the compounds and pharmaceutical compositions containing the salts

By forming specific salts of compounds with multiple basic centers using selected acids at specific ratios, the challenges of achieving stable and soluble salts for drug development are addressed, resulting in salts suitable for treating EGFR exon 20 insertion mutant NSCLC.

JP7665219B2Active Publication Date: 2025-04-21SHENZHEN FORWARD PHARMA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022580228
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-22
Filing Date
2021-06-23
Publication Date
2025-04-21
Estimated Expiration
2041-06-23

AI Technical Summary

Technical Problem

Existing technologies face challenges in predicting and developing salts of compounds with multiple basic centers that exhibit stable chemical and physical properties suitable for drug development, including reasonable salt formation equivalent ratios and solubility.

Method used

The formation of specific salts by reacting compounds of formula (I) with selected acids such as hydrochloric acid, methanesulfonic acid, and maleic acid, at specific equivalent ratios, to achieve salts with improved chemical stability, physical stability, and solubility.

Benefits of technology

The identified salts demonstrate enhanced chemical and physical stability, as well as improved solubility, making them suitable for further drug development, particularly for treating EGFR exon 20 insertion mutant non-small cell lung cancer (NSCLC).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665219000017
    Figure 0007665219000017
  • Figure 0007665219000018
    Figure 0007665219000018
  • Figure 0007665219000019
    Figure 0007665219000019
Patent Text Reader

Abstract

The present application relates to a salt formed from a compound of formula (I) below and an acid, and a method for treating EGFR exon 20 insertion mutant non-small cell lung cancer (NSCLC) using the salt. TIFF2023531077000018.tif36153 [The acid is selected from hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, ethanesulfonic acid, maleic acid, hydrobromic acid, citric acid, L-tartaric acid, and p-toluenesulfonic acid.]
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a salt formed between a compound of formula (I) and an acid. The present application further relates to a method for treating EGFR exon 20 insertion mutant non-small cell lung cancer (NSCLC) using said salt. [ka] [The acid is selected from hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, ethanesulfonic acid, maleic acid, hydrobromic acid, citric acid, L-tartaric acid and p-toluenesulfonic acid.] [Background technology]

[0002] Chinese patent CN105461695B discloses a compound of formula (I) having multiple basic centers, whose inhibitory activity against EGFR activating mutations (such as exon 19 deletion activating mutation, L858R activating mutation, T790M resistance mutation and exon 20 insertion mutation) is significantly higher than that against wild-type EGFR (WT EGFR), and thus has high selectivity and safety, as well as low toxicity and side effects.

[0003] Usually, organic basic compounds with activity are studied for salt formation.However, those skilled in the art cannot predict what stable salts a specific organic basic compound can form with what acid, and cannot predict which of a specific organic basic compound and its acid addition salt is suitable for further drug development, let alone what salt formed has better chemical stability, physical stability or solubility, and what salt has these better properties at the same time.In particular, if an organic basic compound has multiple basic centers, those skilled in the art cannot predict at all whether the salts formed by it with a specific acid at various equivalent ratios have the same properties or different properties, and even more so, cannot predict at all what equivalent ratio of organic basic compound and acid is suitable for further drug development. Summary of the Invention [Problem to be solved by the invention]

[0004] The present application aims to find salts of the compound of formula (I) that are suitable for further drug development. Specifically, the present application aims to find salts that have suitable properties for further drug development, such as a reasonable salt-forming equivalence ratio, better chemical stability, better physical stability, and / or better solubility. [Means for solving the problem]

[0005] According to one aspect of the present invention, the present application relates to a salt formed between a compound of formula (I) and an acid: [ka] [The acid is selected from hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, ethanesulfonic acid, maleic acid, hydrobromic acid, citric acid, L-tartaric acid and p-toluenesulfonic acid.]

[0006] In another aspect of the present invention, the present application relates to a pharmaceutical composition comprising a salt according to the present invention, the pharmaceutical composition comprising a salt according to the present invention and a pharma- ceutically acceptable carrier.

[0007] According to another aspect of the present invention, the present application relates to a method for treating EGFR exon 20 insertion mutant non-small cell lung cancer (NSCLC), comprising administering to a patient a salt according to the present invention.

[0008] According to another aspect of the present invention, the present application relates to the use of a salt according to the present invention for the manufacture of a medicament for the treatment of EGFR exon 20 insertion mutant non-small cell lung cancer (NSCLC). [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is the XRPD pattern of the amorphous free base (sample number: Y11526-45-RV-FWD1509-AF-SU12). [Diagram 2] FIG. 2 is a DSC pattern of the amorphous free base (sample number: Y11526-45-RV-FWD1509-AF-SU12). [Diagram 3] FIG. 3 is a TGA pattern of the amorphous free base (sample number: Y11526-45-RV-FWD1509-AF-SU12). [Figure 4] FIG. 4 is the 1H-NMR pattern of the amorphous free base (sample number: Y11526-45-RV-FWD1509-AF-SU12). [Diagram 5] FIG. 5 is the PLM pattern of the amorphous free base (sample number: Y11526-45-RV-FWD1509-AF-SU12). [Figure 6] FIG. 6 is an XRPD pattern of one equivalent of the amorphous hydrochloride salt (sample number: Y11526-42-SU11-methanol-dichloromethane). [Figure 7] FIG. 7 is a DSC pattern of one equivalent of the amorphous hydrochloride salt (sample number: Y11526-42-SU11-methanol-dichloromethane). [Figure 8] FIG. 8 is a TGA pattern of one equivalent of the amorphous hydrochloride salt (sample number: Y11526-42-SU11-methanol-dichloromethane). [Figure 9] FIG. 9 is the 1H-NMR pattern of one equivalent of the amorphous hydrochloride salt (sample number: Y11526-42-SU11-methanol-dichloromethane). [Figure 10] FIG. 10 is a PLM photograph of one equivalent of the amorphous hydrochloride salt (sample number: Y11526-42-SU11-methanol-dichloromethane). [Figure 11] FIG. 11 is an XRPD pattern of two equivalents of the amorphous hydrochloride salt (sample number: Y11526-28-SU5-methanol-dichloromethane). [Figure 12] FIG. 12 is a DSC pattern of two equivalents of the amorphous hydrochloride salt (sample number: Y11526-28-SU5-methanol-dichloromethane). [Figure 13]FIG. 13 is a TGA pattern of two equivalents of the amorphous hydrochloride salt (sample number: Y11526-28-SU5-methanol-dichloromethane). [Figure 14] FIG. 14 is a 1H-NMR pattern of two equivalents of the amorphous hydrochloride salt (sample number: Y11526-28-SU5-methanol-dichloromethane). [Figure 15] FIG. 15 is a PLM photograph of 2 equivalents of the amorphous hydrochloride salt (sample number: Y11526-28-SU5-methanol-dichloromethane). [Figure 16] FIG. 16 is an XRPD pattern of one equivalent of amorphous methanesulfonate salt (sample number: Y11526-42-SU10-methanol-dichloromethane). [Figure 17] FIG. 17 is a DSC pattern of one equivalent of amorphous methanesulfonate salt (sample number: Y11526-42-SU10-methanol-dichloromethane). [Figure 18] FIG. 18 is a TGA pattern of one equivalent of amorphous methanesulfonate salt (sample number: Y11526-42-SU10-methanol-dichloromethane). [Figure 19] FIG. 19 is a 1H-NMR pattern of one equivalent of amorphous methanesulfonate salt (sample number: Y11526-42-SU10-methanol-dichloromethane). [Figure 20] FIG. 20 is a PLM photograph of one equivalent of amorphous methanesulfonate salt (sample number: Y11526-42-SU10-methanol-dichloromethane). [Figure 21] FIG. 21 is an XRPD pattern of two equivalents of the amorphous methanesulfonate salt (sample number: Y11526-28-SU4-methanol-dichloromethane). [Figure 22] FIG. 22 is a DSC pattern of two equivalents of the amorphous methanesulfonate salt (sample number: Y11526-28-SU4-methanol-dichloromethane). [Diagram 23] FIG. 23 is a TGA pattern of two equivalents of the amorphous methanesulfonate salt (sample number: Y11526-28-SU4-methanol-dichloromethane). [Figure 24] FIG. 24 is a 1H-NMR pattern of two equivalents of the amorphous methanesulfonate salt (sample number: Y11526-28-SU4-methanol-dichloromethane). [Diagram 25] FIG. 25 is a PLM photograph of 2 equivalents of amorphous methanesulfonate salt (sample number: Y11526-28-SU4-methanol-dichloromethane). [Figure 26] is the XRPD pattern of one equivalent of amorphous benzenesulfonate salt (sample number: Y11526-42-SU9-methanol-dichloromethane). [Figure 27] FIG. 27 is a DSC pattern of one equivalent of amorphous benzenesulfonate salt (sample number: Y11526-42-SU9-methanol-dichloromethane). [Figure 28] FIG. 28 is a TGA pattern of one equivalent of amorphous benzenesulfonate salt (sample number: Y11526-42-SU9-methanol-dichloromethane). [Figure 29] FIG. 29 is a 1H-NMR pattern of one equivalent of amorphous benzenesulfonate salt (sample number: Y11526-42-SU9-methanol-dichloromethane). [Diagram 30] FIG. 30 is a PLM photograph of one equivalent of amorphous benzenesulfonate (sample number: Y11526-42-SU9-methanol-dichloromethane). [Diagram 31] FIG. 31 is an XRPD pattern of two equivalents of amorphous benzenesulfonate salt (sample number: Y11526-30-SU1-water). [Diagram 32] FIG. 32 is a DSC pattern of two equivalents of amorphous benzenesulfonate salt (sample number: Y11526-30-SU1-water). [Diagram 33] FIG. 33 is a TGA pattern of two equivalents of amorphous benzenesulfonate salt (sample number: Y11526-30-SU1-water). [Diagram 34] FIG. 34 is a 1H-NMR pattern of two equivalents of amorphous benzenesulfonate (sample number: Y11526-30-SU1-water). [Diagram 35]FIG. 35 is a PLM photograph of 2 equivalents of amorphous benzenesulfonate (sample number: Y11526-30-SU1-water). [Diagram 36] FIG. 36 is an XRPD pattern of one equivalent of amorphous ethanesulfonate salt (sample number: Y11526-28-SU7-methanol-dichloromethane). [Figure 37] FIG. 37 is a DSC pattern of one equivalent of amorphous ethanesulfonate salt (sample number: Y11526-28-SU7-methanol-dichloromethane). [Figure 38] FIG. 38 is a TGA pattern of one equivalent of amorphous ethanesulfonate salt (sample number: Y11526-28-SU7-methanol-dichloromethane). [Figure 39] FIG. 39 is the 1H-NMR pattern of one equivalent of amorphous ethanesulfonate salt (sample number: Y11526-28-SU7-methanol-dichloromethane). [Diagram 40] FIG. 40 is a PLM photograph of one equivalent of amorphous ethanesulfonate salt (sample number: Y11526-28-SU7-methanol-dichloromethane). [Diagram 41] FIG. 41 is an XRPD pattern of one equivalent of amorphous maleate salt (sample number: Y11526-30-SU2-water). [Diagram 42] FIG. 42 is a DSC pattern of one equivalent of amorphous maleate salt (sample number: Y11526-30-SU2-water). [Diagram 43] FIG. 43 is a TGA pattern of one equivalent of amorphous maleate salt (sample number: Y11526-30-SU2-water). [Diagram 44] FIG. 44 is the 1H-NMR pattern of one equivalent of amorphous maleate salt (sample number: Y11526-30-SU2-water). [Diagram 45] FIG. 45 is a PLM photograph of 1 equivalent of amorphous maleate salt (sample number: Y11526-30-SU2-water). [Diagram 46]FIG. 46 is an XRPD pattern of one equivalent of the crystalline hydrobromide salt (sample number: Y11526-33-SU8-methanol-dichloromethane). [Figure 47] FIG. 47 is a DSC pattern of one equivalent of the crystalline hydrobromide salt (sample number: Y11526-33-SU8-methanol-dichloromethane). [Figure 48] FIG. 48 is a TGA pattern of one equivalent of the crystalline hydrobromide salt (sample number: Y11526-33-SU8-methanol-dichloromethane). [Figure 49] FIG. 49 is the 1H-NMR pattern of one equivalent of the crystalline hydrobromide salt (sample number: Y11526-33-SU8-methanol-dichloromethane). [Figure 50] FIG. 50 is a PLM photograph of one equivalent of the crystalline hydrobromide salt (sample number: Y11526-33-SU8-methanol-dichloromethane). [Figure 51] FIG. 51 is the XRPD pattern of the amorphous nitrate salt (sample number: Y11526-18-RV7-methanol-dichloromethane). [Figure 52] FIG. 52 is the 1H-NMR pattern of the amorphous nitrate salt (sample number: Y11526-18-RV7-methanol-dichloromethane). [Figure 53] FIG. 53 is an XRPD pattern of the amorphous sulfate salt (sample number: Y11526-15-RV3-methanol-acetonitrile). [Figure 54] FIG. 54 is a DSC pattern of the amorphous sulfate salt (sample number: Y11526-15-RV3-methanol-acetonitrile). [Figure 55] FIG. 55 is a TGA pattern of the amorphous sulfate salt (sample number: Y11526-15-RV3-methanol-acetonitrile). [Figure 56] FIG. 56 is the 1H-NMR pattern of the amorphous sulfate salt (sample number: Y11526-15-RV3-methanol-acetonitrile). [Figure 57]FIG. 57 is a PLM photograph of the amorphous sulfate salt (sample number: Y11526-15-RV3-methanol-acetonitrile). [Figure 58] FIG. 58 is an XRPD pattern of 2 equivalents of amorphous p-toluenesulfonate salt (sample number: Y11526-23-FD11-water). [Figure 59] FIG. 59 is a DSC pattern of 2 equivalents of amorphous p-toluenesulfonate salt (sample number: Y11526-23-FD11-water). [Figure 60] FIG. 60 is a TGA pattern of 2 equivalents of amorphous p-toluenesulfonate salt (sample number: Y11526-23-FD11-water). [Figure 61] FIG. 61 is the 1H-NMR pattern of 2 equivalents of amorphous p-toluenesulfonate salt (sample number: Y11526-23-FD11-water). [Figure 62] FIG. 62 is a PLM photograph of 2 equivalents of amorphous p-toluenesulfonate salt (sample number: Y11526-23-FD11-water). [Figure 63] FIG. 63 is a photograph of 2 equivalents of amorphous p-toluenesulfonate salt (sample number: Y11526-23-FD11-water). [Figure 64] FIG. 64 is an XRPD pattern of amorphous sulfosalicylate (sample number: Y11526-25-FD13-1,4-dioxane). [Figure 65] FIG. 65 is a DSC pattern of amorphous sulfosalicylate (sample number: Y11526-25-FD13-1,4-dioxane). [Figure 66] FIG. 66 is a TGA pattern of amorphous sulfosalicylate (sample number: Y11526-25-FD13-1,4-dioxane). [Figure 67] FIG. 67 is the 1H-NMR pattern of amorphous sulfosalicylate (sample number: Y11526-25-FD13-1,4-dioxane). [Figure 68] FIG. 68 is a PLM photograph of amorphous sulfosalicylate (sample number: Y11526-25-FD13-1,4-dioxane). [Figure 69] FIG. 69 is an XRPD pattern of amorphous sulfosalicylate (sample number: Y11526-25-FD12-1,4-dioxane). [Figure 70] FIG. 70 is a DSC pattern of amorphous sulfosalicylate (sample number: Y11526-25-FD12-1,4-dioxane). [Figure 71] FIG. 71 is a TGA pattern of amorphous sulfosalicylate (sample number: Y11526-25-FD12-1,4-dioxane). [Figure 72] FIG. 72 is the 1H-NMR pattern of amorphous sulfosalicylate (sample number: Y11526-25-FD12-1,4-dioxane). [Figure 73] FIG. 73 is a PLM photograph of amorphous sulfosalicylate (sample number: Y11526-25-FD12-1,4-dioxane). [Figure 74] FIG. 74 is an XRPD pattern of the amorphous L-malate salt (sample number: Y11526-17-RV6-methanol-dichloromethane). [Figure 75] FIG. 75 is a DSC pattern of the amorphous L-malate salt (sample number: Y11526-17-RV6-methanol-dichloromethane). [Figure 76] FIG. 76 is a TGA pattern of the amorphous L-malate salt (sample number: Y11526-17-RV6-methanol-dichloromethane). [Figure 77] FIG. 77 is the 1H-NMR pattern of the amorphous L-malate salt (sample number: Y11526-17-RV6-methanol-dichloromethane). [Figure 78] FIG. 78 is a PLM photograph of amorphous L-malate salt (sample number: Y11526-17-RV6-methanol-dichloromethane). [Figure 79] FIG. 79 is an XRPD pattern of one equivalent of amorphous citrate salt (sample number: Y11526-10-FD6-1,4-dioxane). [Figure 80]FIG. 80 is a DSC pattern of one equivalent of amorphous citrate salt (sample number: Y11526-10-FD6-1,4-dioxane). [Figure 81] FIG. 81 is a TGA pattern of one equivalent of amorphous citrate salt (sample number: Y11526-10-FD6-1,4-dioxane). [Figure 82] FIG. 82 is the 1H-NMR pattern of one equivalent of amorphous citrate salt (sample number: Y11526-10-FD6-1,4-dioxane). [Figure 83] FIG. 83 is a PLM photograph of 1 equivalent of amorphous citrate salt (sample number: Y11526-10-FD6-1,4-dioxane). [Figure 84] FIG. 84 is an XRPD pattern of one equivalent of amorphous L-tartrate salt (sample number: Y11526-10-FD7-1,4-dioxane). [Figure 85] FIG. 85 is a DSC pattern of one equivalent of amorphous L-tartrate salt (sample number: Y11526-10-FD7-1,4-dioxane). [Figure 86] FIG. 86 is a TGA pattern of one equivalent of amorphous L-tartrate salt (sample number: Y11526-10-FD7-1,4-dioxane). [Figure 87] FIG. 87 is the 1H-NMR pattern of one equivalent of amorphous L-tartrate salt (sample number: Y11526-10-FD7-1,4-dioxane). [Figure 88] FIG. 88 is an overlay of the HPLC pattern of one equivalent of amorphous L-tartrate salt (sample number: Y11526-10-FD7-1,4-dioxane). [Figure 89] FIG. 89 is an XRPD overlay of solid storage safety testing of amorphous free base, in which, from top to bottom, the first trace is the XRPD of the control crystalline free base, the second trace is the XRPD of the solid obtained in test BS2, the third trace is the XRPD of the solid obtained in test BS1, and the fourth trace is the XRPD of the original solid. [Figure 90]FIG. 90 is an XRPD overlay of a solid storage safety study of one equivalent of the amorphous hydrochloride salt, in which the upper trace is the XRPD of the solid obtained in study BS2, the middle trace is the XRPD of the solid obtained in study BS1, and the lower trace is the XRPD of the original solid. [Figure 91] FIG. 91 is an XRPD overlay of solid storage safety testing of two equivalents of the amorphous hydrochloride salt, in which the upper trace is the XRPD of the solid obtained in test BS2, the middle trace is the XRPD of the solid obtained in test BS1, and the lower trace is the XRPD of the original solid. [Figure 92] FIG. 92 is a photograph of a solid storage safety test of two equivalents of the amorphous hydrochloride salt, in which the picture on the left is a photograph of the original solid and the picture on the right is a photograph of the solid obtained in test BS1. [Figure 93] FIG. 93 is an XRPD overlay of a solid storage safety study of one equivalent of the amorphous methanesulfonate salt, in which the upper trace is the XRPD of the solid obtained in study BS2, the middle trace is the XRPD of the solid obtained in study BS1, and the lower trace is the XRPD of the original solid. [Figure 94] FIG. 94 is an XRPD overlay of a solid storage safety test of two equivalents of the amorphous methanesulfonate salt, in which the upper trace is the XRPD of the solid obtained in test BS2, the middle trace is the XRPD of the solid obtained in test BS1, and the lower trace is the XRPD of the original solid. [Figure 95] FIG. 95 is a photograph of two equivalents of amorphous methanesulfonate salt in a solid storage safety test, in which the left picture is a photograph of the original solid, the middle picture is a photograph of the solid obtained in test BS1, and the right picture is a photograph of the solid obtained in test BS2. [Figure 96]FIG. 96 is an XRPD overlay of a solid storage safety test of one equivalent of amorphous benzenesulfonate salt, in which the upper trace is the XRPD of the solid obtained in test BS2, the middle trace is the XRPD of the solid obtained in test BS1, and the lower trace is the XRPD of the original solid. [Figure 97] FIG. 97 shows photographs of two equivalents of amorphous benzenesulfonate in a solid storage safety test, in which the picture on the left is a photograph of the original solid, and the picture on the right is a photograph of the solid obtained in test BS1. [Figure 98] FIG. 98 is an XRPD overlay of a solid storage safety test of two equivalents of amorphous benzenesulfonate salt, in which the upper trace is the XRPD of the solid obtained in test BS2 and the lower trace is the XRPD of the original solid. [Figure 99] FIG. 99 is a photograph of one equivalent of amorphous ethanesulfonate salt in a solid storage safety test, in which the picture on the left is a photograph of the original solid, and the picture on the right is a photograph of the solid obtained in test BS1. [Figure 100] FIG. 100 is an XRPD overlay of a solid storage safety study of one equivalent of amorphous ethanesulfonate salt, in which the upper trace is the XRPD of the solid obtained in study BS2 and the lower trace is the XRPD of the original solid. [Figure 101] FIG. 101 is an XRPD overlay of solid storage safety testing of one equivalent of amorphous maleate salt, in which the upper trace is the XRPD of the solid obtained in test BS2, the middle trace is the XRPD of the solid obtained in test BS1, and the lower trace is the XRPD of the original solid. [Figure 102] FIG. 102 is a photograph of one equivalent of amorphous maleate in a solid storage safety test, in which the picture on the left is a photograph of the original solid and the picture on the right is a photograph of the solid obtained in test BS1. [Figure 103]FIG. 103 is an XRPD overlay of solid storage safety testing of one equivalent of the crystalline hydrobromide salt, in which the upper trace is the XRPD of the solid obtained in test BS2, the middle trace is the XRPD of the solid obtained in test BS1, and the lower trace is the XRPD of the original solid. [Figure 104] FIG. 104 is an XRPD pattern of the solid obtained in a 2-hour solid solubility test of one equivalent of the crystalline hydrobromide salt, where the upper trace is the XRPD of the solid obtained in the 2-hour solid solubility test and the lower trace is the XRPD of the original solid. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In one embodiment, the present invention relates to a salt formed between a compound of formula (I) and an acid. [ka] [The acid is selected from hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, ethanesulfonic acid, maleic acid, hydrobromic acid, citric acid, L-tartaric acid and p-toluenesulfonic acid. Preferably, the acid is selected from hydrochloric acid, methanesulfonic acid and maleic acid.] More preferably, the equivalent ratio of the compound of formula (I) to the acid is 1:1 or 1:2. Even more preferably, the acid is methanesulfonic acid. Even more preferably, the equivalent ratio of the compound of formula (I) to the acid is 1:1.

[0011] The inventors of the present application have unexpectedly found that when the compound of formula (I) is reacted with an organic or inorganic acid, the compound of formula (I) can form salts with some acids, but cannot form salts with other acids at all.

[0012] Even more surprisingly, when the compound of formula (I) is reacted with hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, ethanesulfonic acid, maleic acid, hydrobromic acid, sulfosalicylic acid, L-malic acid, citric acid or L-tartaric acid at a molar ratio of the compound of formula (I) to acid=1:1, some of the salts formed have a stoichiometric ratio of the compound of formula (I) to acid=1:1, but the compound of formula (I) cannot form any salts with some acids at a stoichiometric ratio of the compound of formula (I) to acid=1:1. Specifically, Hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, ethanesulfonic acid, maleic acid, hydrobromic acid, citric acid and L-tartaric acid can give salts having a stoichiometric ratio of the compound of formula (I) to acid of 1:1 (the corresponding salts are hereinafter referred to as 1 equivalent of hydrochloride, 1 equivalent of methanesulfonate, 1 equivalent of benzenesulfonate, 1 equivalent of ethanesulfonate, 1 equivalent of maleate, 1 equivalent of hydrobromide, 1 equivalent of citrate and 1 equivalent of L-tartrate, respectively), whereas sulfosalicylic acid and L-malic acid cannot give salts having a stoichiometric ratio of the compound of formula (I) to acid of 1:1.

[0013] Furthermore, it is even more surprising that, when the compound of formula (I) is reacted with hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, nitric acid, sulfuric acid, p-toluenesulfonic acid or sulfosalicylic acid in a molar ratio of the compound of formula (I) to the acid of 1:2, some of the salts formed have a stoichiometric ratio of the compound of formula (I) to the acid of 1:2, but the compound of formula (I) is reacted with some of the acids in a molar ratio of 1:2. It is not possible to form a salt with a stoichiometric ratio of compound:acid=1:2. Hydrochloric acid, methanesulfonic acid, benzenesulfonic acid and p-toluenesulfonic acid can give a salt having a stoichiometric ratio of the compound of formula (I) to acid of 1:2 (the corresponding salts are hereinafter referred to as 2 equivalents of hydrochloride, 2 equivalents of methanesulfonate, 2 equivalents of benzenesulfonate and 2 equivalents of p-toluenesulfonate, respectively), whereas nitric acid, sulfuric acid and sulfosalicylic acid cannot give a salt having a stoichiometric ratio of the compound of formula (I) to acid of 1:2.

[0014] More specifically, the salts obtained as above include 1 equivalent of hydrochloride, 1 equivalent of methanesulfonate, 1 equivalent of benzenesulfonate, 1 equivalent of ethanesulfonate, 1 equivalent of maleate, 1 equivalent of hydrobromide, 1 equivalent of citrate, 1 equivalent of L-tartrate, 2 equivalents of hydrochloride, 2 equivalents of methanesulfonate, 2 equivalents of benzenesulfonate and 2 equivalents of p-toluenesulfonate, as well as sulfosalicylate, L-malate, nitrate and sulfate salts that do not have a reasonable salt-forming equivalent ratio. For example, salts obtained as described above include 1 equivalent of amorphous hydrochloride, 1 equivalent of amorphous methanesulfonate, 1 equivalent of amorphous benzenesulfonate, 1 equivalent of amorphous ethanesulfonate, 1 equivalent of amorphous maleate, 1 equivalent of crystalline hydrobromide, 1 equivalent of amorphous citrate, 1 equivalent of amorphous L-tartrate, 2 equivalents of amorphous hydrochloride, 2 equivalents of amorphous methanesulfonate, 2 equivalents of amorphous benzenesulfonate and 2 equivalents of amorphous p-toluenesulfonate, as well as amorphous sulfosalicylate, amorphous L-malate, amorphous nitrate and amorphous sulfate salts that do not have reasonable salt forming equivalent ratios.

[0015] For the development of drugs, it is extremely important whether the salt obtained as described above has chemical and physical stability at the end of production. The chemical and physical stability of the salt at the end of production is as follows: the chemical stability of the salt at the end of its preparation, i.e., the purity of the salt obtained at the end of its preparation does not decrease significantly compared to the purity of the free base from which it is prepared; and The physical stability of the salt at the end of its production, i.e., the salt does not immediately undergo crystal form conversion, moisture absorption and / or discoloration at the end of its production; Includes.

[0016] Chemical and physical stability at the end of production revealed that different salts have different performances and it is unpredictable how a salt will perform. One equivalent of citrate, one equivalent of L-tartrate, nitrate and L-malate are chemically unstable at the end of production. Two equivalents of p-toluenesulfonate and sulfate are physically unstable at the end of the manufacturing process; and One equivalent of the hydrochloride, two equivalents of the hydrochloride, one equivalent of the methanesulfonate, two equivalents of the methanesulfonate, one equivalent of the benzenesulfonate, two equivalents of the benzenesulfonate, one equivalent of the ethanesulfonate, one equivalent of the maleate, one equivalent of the hydrobromide and one equivalent of the sulfosalicylate are chemically and physically stable at the end of the preparation.

[0017] The salts having a reasonable salt-forming equivalent ratio as described above and being chemically and physically stable at the end of production include 1 equivalent of hydrochloride, 2 equivalents of hydrochloride, 1 equivalent of methanesulfonate, 2 equivalents of methanesulfonate, 1 equivalent of benzenesulfonate, 2 equivalents of benzenesulfonate, 1 equivalent of ethanesulfonate, 1 equivalent of maleate and 1 equivalent of hydrobromide. Whether these salts have chemical and physical stability even after storage is also very important for drug development. The chemical and physical stability of the salts after storage are as follows: the chemical stability of the salt after storage, i.e., the purity of the salt after storage does not decrease significantly compared to the purity of the salt before storage; and The physical stability of the salt after storage, i.e., the salt does not undergo crystal form conversion, moisture absorption and / or discoloration before and after storage; Includes.

[0018] In terms of chemical and physical stability after storage, different salts have different performances, and it is unpredictable how a certain salt will perform. In terms of chemical and physical stability after storage, different salts have different performances, and it is unpredictable how a certain salt will perform. One equivalent of the hydrochloride, one equivalent of the benzenesulfonate and one equivalent of the maleate are chemically unstable under the storage conditions of "solid / 25°C / 60%RH / open / 1 week" and / or "solid / 60°C / closed container / 1 week". 2 equivalents of the hydrochloride, 2 equivalents of the methanesulfonate, 2 equivalents of the benzenesulfonate, 1 equivalent of the ethanesulfonate and 1 equivalent of the maleate are physically unstable under the storage conditions of "solid / 25°C / 60%RH / open / 1 week" and / or "solid / 60°C / closed container / 1 week"; and One equivalent of the methanesulfonate salt and one equivalent of the hydrobromide salt are chemically and physically stable under the storage conditions of "solid / 25°C / 60%RH / open / 1 week" and "solid / 60°C / closed container / 1 week."

[0019] The salts having a reasonable salt-forming equivalent ratio as described above and being chemically and physically stable at the end of production include 1 equivalent of hydrochloride, 2 equivalents of hydrochloride, 1 equivalent of methanesulfonate, 2 equivalents of methanesulfonate, 1 equivalent of benzenesulfonate, 2 equivalents of benzenesulfonate, 1 equivalent of ethanesulfonate, 1 equivalent of maleate and 1 equivalent of hydrobromide. Whether these salts have better solubility is also very important for drug development. The fact that different salts have different solubilities makes it clear that it is unpredictable what kind of solubility a certain salt has. Specifically, Two equivalents of the benzenesulfonate salt and one equivalent of the hydrobromide salt do not meet the solubility of 2 mg / mL in several solvents that simulate physiological conditions; and 1 equivalent of the hydrochloride, 2 equivalents of the hydrochloride, 1 equivalent of the methanesulfonate, 2 equivalents of the methanesulfonate, 1 equivalent of the benzenesulfonate, 1 equivalent of the ethanesulfonate and 1 equivalent of the maleate salt have solubilities of greater than 2 mg / mL in a variety of solvents simulating physiological conditions.

[0020] As can be seen from the above, one equivalent of the methanesulfonate salt surprisingly and unexpectedly has a reasonable salt formation equivalent ratio, better chemical stability, better physical stability and better solubility at the same time, making it a suitable salt of the compound of formula (I) for further drug development.

[0021] In another aspect of the present invention, the present application relates to a pharmaceutical composition comprising a salt according to the present invention, the pharmaceutical composition comprising a salt according to the present invention and a pharma- ceutically acceptable carrier.

[0022] According to another aspect of the present invention, the present application relates to a method for treating EGFR exon 20 insertion mutant non-small cell lung cancer (NSCLC), comprising administering to a patient a salt according to the present invention.

[0023] According to another aspect of the present invention, the present application relates to the use of a salt according to the present invention for the manufacture of a medicament for the treatment of EGFR exon 20 insertion mutant non-small cell lung cancer (NSCLC). EXAMPLES

[0024] The present application is illustrated by the following examples.

[0025] Working Example In the examples, the following test conditions are used: [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6] [Table 7]

[0026] The concentration of free base and the concentration of acid group ions in the same sample are measured by IC, and then the stoichiometric ratio of base:acid in that sample is calculated as follows:

number

[0027] Example 1: Amorphous Free Base (Sample Number: Y11526-45-RV-FWD1509- AF-SU12) Approximately 300 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask, and 10 mL of methanol / acetonitrile (v:v=1:1) was added to obtain a clear solution. The clear solution was subjected to high speed volatilization (i.e., rotary evaporation) to remove the solvent, obtaining approximately 290 mg of an off-white solid, with a yield of approximately 97%. HPLC showed the product to be 99.9% pure. PLM showed the product to be an irregular sample (Figure 5). XRPD showed the product to be amorphous (Figure 1). DSC showed the product had glass transition temperatures of 68.4°C and 104.7°C (Figure 2). TGA showed the product had a weight loss of about 5.1% at 150°C (Figure 3). The amorphous free base (sample number: Y11526-45-RV-FWD1509-AF-SU12) is chemically and physically stable at the end of manufacture.

[0028] Example 2: 1 equivalent of amorphous hydrochloride (sample number: Y11526-42-SU11-methanol-dichloromethane) Approximately 300 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask, and 20 mL of methanol / dichloromethane (v:v=1:1) and 1 equivalent of a diluted solution of hydrochloric acid (518 μL, 44 mg / mL, in methanol / dichloromethane (v:v=1:1)) were added and reacted at 50° C. for 2 hours to obtain a clear solution. The solvent of the clear solution was removed by high-speed volatilization to obtain approximately 306 mg of a pale yellow solid, with a yield of approximately 95%. HPLC showed the product was 99.9% pure. PLM showed the product was an irregular sample (Figure 10). XRPD showed the product was amorphous (Figure 6). DSC showed the product had a glass transition temperature of 128.5°C (Figure 7). TGA showed the product had a weight loss of about 5.1% at 150°C (Figure 8). IC showed the product had a free base concentration of 0.5 mg / mL and a chloride ion concentration of 33.7 mg / L, resulting in a base:acid stoichiometry of about 1:1 in the product. One equivalent of the amorphous hydrochloride salt (sample number: Y11526-42-SU11-methanol-dichloromethane) is chemically and physically stable at the end of the preparation and is reasonable in terms of base:acid stoichiometry.

[0029] Example 3: 2 equivalents of amorphous hydrochloride (sample number: Y11526-28-SU5-methanol-dichloromethane) Approximately 300 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask, and 5 mL of methanol / dichloromethane (v:v=1:1) and 2 equivalents of a diluted solution of hydrochloric acid (1010 μL, 44 mg / mL, in methanol / dichloromethane (v:v=1:1)) were added, and the mixture was reacted at 50°C for 2 hours, cooled to 25°C, and reacted for another 2 hours to obtain a clear solution. The solvent was removed from the obtained clear solution by high-speed volatilization to obtain approximately 310 mg of a yellow solid, with a yield of approximately 90%. HPLC showed the product was 99.9% pure. PLM showed the product was an irregular sample (Figure 15). XRPD showed the product was amorphous (Figure 11). DSC showed the product had a glass transition temperature of 154.0°C (Figure 12). TGA showed the product had a weight loss of about 4.3% at 110°C (Figure 13). IC showed the product had a free base concentration of 0.5 mg / mL and chloride ion concentration of 77.4 mg / L, giving a base:acid stoichiometry of about 1:2 in the product. Two equivalents of the amorphous hydrochloride salt (sample number: Y11526-28-SU5-methanol-dichloromethane) are chemically and physically stable at the end of the preparation and are reasonable in terms of base:acid stoichiometry.

[0030] Example 4: 1 equivalent of amorphous methanesulfonate salt (sample number: Y11526-42-SU10-methanol-dichloromethane) The weighed out compound of formula (I) was added to acetone (11.70 times the weight of the compound of formula (I)) while stirring, and the temperature was raised to 45-55°C. After dissolution, the reaction mixture was filtered while still hot, the filtrate was heated to 45-55°C, water (1 times the weight of the compound of formula (I)) was added, stirring was continued at 45-55°C, methanesulfonic acid (0.188 times the weight of the compound of formula (I)) was added dropwise within 30 minutes, and the mixture was stirred at 45-55°C for 60±10 minutes. The reaction mixture was cooled to 20-30°C within 1.0-2.0 hours, crystallized, and crystallized for 1.0-2.0 hours while stirring at 10-30°C. The reaction mixture was filtered, and the filter cake was washed twice with acetone (0.78 times the weight of the compound of formula (I) × 2). The filter cake was dried to constant weight at 40±5° C. and ≦−0.07 MPa to give a highly crystalline material. Approximately 300 mg of the resulting highly crystalline material was taken, and approximately 50 mL of methanol / dichloromethane (v:v=1:1) was added to obtain a clear solution. The solvent was removed from the clear solution by high speed volatilization to obtain approximately 268 mg of a pale yellow solid, with a yield of approximately 72%. HPLC showed the product to be 99.9% pure. PLM showed the product to be an irregular sample (Figure 20). XRPD showed the product to be amorphous (Figure 16). DSC showed the product had a glass transition temperature of 111.1°C (Figure 17). TGA showed the product had a weight loss of about 3.9% at 140°C (Figure 18). 1 H-NMR showed that the base:acid stoichiometry in the product was approximately 1:1 (Figure 19). One equivalent of amorphous methanesulfonate salt (sample number: Y11526-42-SU10-methanol-dichloromethane) is chemically and physically stable at the end of preparation and is reasonable in terms of base:acid stoichiometry.

[0031] Example 5: 2 equivalents of amorphous methanesulfonate (sample number: Y11526-28-SU4-methanol-dichloromethane) Approximately 300 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask. 2 mL of methanol and 2 equivalents of a diluted solution of methanesulfonic acid (798 μL, 148 mg / mL, in methanol) were added, and the solution turned from clear to yellow and opaque. 2 mL of dichloromethane was added, and the solution became clear, followed by the addition of 1 mL of methanol / dichloromethane (v:v=1:1). The reaction was carried out at 50°C for 2 hours, and then the temperature was lowered to 25°C and the reaction was continued for about 3 hours to obtain a clear solution. The solvent was removed from the obtained clear solution by high-speed volatilization to obtain about 380 mg of a yellow solid, with a yield of about 85%. HPLC showed the product to be 99.9% pure. PLM showed the product to be an irregular sample (Figure 25). XRPD showed the product to be amorphous (Figure 21). DSC showed the product had a glass transition temperature of 131.7°C (Figure 22). TGA showed the product had a weight loss of about 2.4% at 130°C (Figure 23). 1 H-NMR showed that the base:acid stoichiometry in the product was approximately 1:2 (Figure 24). Two equivalents of amorphous methanesulfonate (sample number: Y11526-28-SU4-methanol-dichloromethane) is chemically and physically stable at the end of preparation and has a reasonable base:acid stoichiometry.

[0032] Example 6: 1 equivalent of amorphous benzenesulfonate (sample number: Y11526-42-SU9-methanol-dichloromethane) Approximately 300 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 250 mL round-bottom flask with 1 equivalent of benzenesulfonic acid, 15 mL of water was added, and the mixture was reacted at 50° C. for 2 hours, after which a clear solution was obtained and a solid precipitated. The suspension was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then the water was removed by freeze-drying to obtain a low crystallinity sample. The freeze-dried sample was dissolved in 5 mL of methanol / dichloromethane (v:v=1:1) to obtain a clear solution. The clear solution was subjected to high-speed volatilization to remove the solvent, yielding about 320 mg of a pale yellow solid, with a yield of about 83%. HPLC showed the product to be 99.7% pure. PLM showed the product to be an irregular sample (Figure 30). XRPD showed the product to be amorphous (Figure 26). DSC showed the product had glass transition temperatures of 100.7°C and 114.7°C (Figure 27). TGA showed the product had a weight loss of about 3.8% at 150°C (Figure 28). 1 H-NMR showed that the base:acid stoichiometry in the product was approximately 1:1 (Figure 29). One equivalent of amorphous benzenesulfonate (sample number: Y11526-42-SU9-methanol-dichloromethane) is chemically and physically stable at the end of preparation and is reasonable in terms of base:acid stoichiometry.

[0033] Example 7: 2 equivalents of amorphous benzenesulfonate (sample number: Y11526-30-SU1-water) About 300 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 250 mL round-bottom flask with 2 equivalents of benzenesulfonic acid, and 15 mL of water was added and reacted at 50° C. for 2 hours to obtain a clear solution. The obtained clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then the water was removed by freeze-drying to obtain about 380 mg of a yellow solid, with a yield of about 81%. HPLC showed the product to be 99.7% pure. PLM showed the product to be an irregular sample (Figure 35). XRPD showed the product to be amorphous (Figure 31). DSC showed the product had no glass transition temperature (Figure 32). TGA showed the product had a weight loss of about 1.9% at 100°C (Figure 33). 1 H-NMR showed that the base:acid stoichiometry in the product was approximately 1:2 (Figure 34). Two equivalents of amorphous benzenesulfonate (sample number: Y11526-30-SU1-water) is chemically and physically stable at the end of the preparation and has a reasonable base:acid stoichiometry.

[0034] Example 8: 1 equivalent of amorphous ethanesulfonate salt (sample number: Y11526-28-SU7-methanol-dichloromethane) Approximately 300 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask, and 5 mL of methanol / dichloromethane (v:v=1:1) and 1 equivalent of a diluted solution of ethanesulfonic acid (541 μL, 128 mg / mL, in methanol / dichloromethane (v:v=1:1)) were added, and the mixture was reacted at 50° C. for 2 hours, cooled to 25° C., and reacted for another 2 hours to obtain a clear solution. The solvent was removed from the obtained clear solution by high-speed volatilization to obtain approximately 340 mg of a yellow solid, with a yield of approximately 90%. HPLC showed the product to be 99.9% pure. PLM showed the product to be an irregular sample (Figure 40). XRPD showed the product to be amorphous (Figure 36). DSC showed the product had a glass transition temperature of 102.4°C (Figure 37). TGA showed the product had a weight loss of about 1.6% at 101°C (Figure 38). 1 H-NMR showed that the base:acid stoichiometry in the product was approximately 1:1 (Figure 39). One equivalent of amorphous ethanesulfonate salt (sample number: Y11526-28-SU7-methanol-dichloromethane) is chemically and physically stable at the end of preparation and is reasonable in terms of base:acid stoichiometry.

[0035] Example 9: 1 equivalent of amorphous maleate salt (sample number: Y11526-30-SU2-water) About 300 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 250 mL round-bottom flask with 1 equivalent of maleic acid, and 20 mL of water was added and reacted at 50° C. for 2 hours to obtain a clear solution. The obtained clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then the water was removed by freeze-drying to obtain about 330 mg of a pale yellow solid, with a yield of about 89%. HPLC showed the product to be 99.9% pure. PLM showed the product to be an irregular sample (Figure 45). XRPD showed the product to be amorphous (Figure 41). DSC showed the product had glass transition temperatures of 89.2°C and 125.2°C (Figure 42). TGA showed the product had a weight loss of about 0.9% at 100°C (Figure 43). 1 H-NMR showed that the base:acid stoichiometry in the product was approximately 1:1 (Figure 44). One equivalent of amorphous maleate salt (sample number: Y11526-30-SU2-water) is chemically and physically stable at the end of the preparation and is reasonable in terms of base:acid stoichiometry.

[0036] Example 10: 1 equivalent of crystalline hydrobromide salt (sample number: Y11526-33-SU8-methanol-dichloromethane) Approximately 300 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask, and 20 mL of methanol / dichloromethane (v:v=1:1) and 1 equivalent of a diluted solution of hydrobromic acid (728 μL, 70 mg / mL, in methanol / dichloromethane (v:v=1:1)) were added and reacted at 50° C. for 2 hours to obtain a nearly clear solution (with a trace amount of insoluble impurities). The impurities were filtered through a 0.45 μm filter membrane to obtain a clear solution, and the obtained clear solution was subjected to solvent removal by high-speed volatilization to obtain approximately 310 mg of a pale yellow solid, with a yield of approximately 90%. HPLC showed the product was 99.9% pure. PLM showed the product was rod-like and chunky sample (Figure 50). XRPD showed the product had high crystallinity (Figure 46). DSC showed the product started to dehydrate at about 30°C (Figure 47). TGA showed the product had a weight loss of about 1.8% at 110°C (Figure 48). KF showed the product contained 1.9% water. IC showed the product had a free base concentration of 0.5 mg / mL and bromide ion concentration of 68.1 mg / L, so the base:acid stoichiometry in the product is about 1:1. One equivalent of the crystalline hydrobromide salt (sample number: Y11526-33-SU8-methanol-dichloromethane) is chemically and physically stable at the end of preparation and has a reasonable base:acid stoichiometry.

[0037] Example 11: Amorphous Nitrate (Sample Number: Y11526-18-RV7-Methanol-Dichloromethane) Approximately 100 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask, 10 mL of 1,4-dioxane was added, and reacted with 2 equivalents of a diluted solution of nitric acid (144 μL, 180 mg / mL, in 1,4-dioxane) at 50° C. for 2 hours. The resulting clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then the 1,4-dioxane was removed by freeze-drying to obtain a nearly amorphous material. Approximately 80 mg of the resulting near-amorphous material was weighed out and placed in a 40 mL glass flask, and approximately 10 mL of methanol / dichloromethane (v:v=1:1) was added to obtain a clear solution. The solvent was removed from the clear solution by high-speed volatilization to obtain the amorphous nitrate salt. XRPD showed the product to be amorphous (Figure 51). 1 H-NMR showed the occurrence of decomposition of the product (Figure 52). The amorphous nitrate (sample number: Y11526-18-RV7-methanol-dichloromethane) is at least chemically unstable at the end of its production run.

[0038] Example 12: Amorphous Sulfate (Sample Number: Y11526-15-RV3-Methanol-Acetonitrile) Approximately 100 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask, 10 mL of 1,4-dioxane was added, and 2 equivalents of a diluted sulfuric acid solution (228 μL, 180.3 mg / mL, in 1,4-dioxane) was added, and the mixture was reacted for 2 hours at 50° C. The resulting clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then the 1,4-dioxane was removed by freeze-drying to obtain a nearly amorphous material. Approximately 80 mg of the resulting near-amorphous material was taken and placed in a 40 mL glass flask, and approximately 10 mL of methanol / acetonitrile (v:v=1:1) was added to obtain a clear solution. The solvent was removed from the clear solution by high-speed volatilization to obtain the amorphous sulfate salt. HPLC showed that the purity of the product was 99.7%. PLM showed that the product was an irregular sample (Figure 57). XRPD showed that the product was amorphous (Figure 53). DSC showed that the glass transition temperatures of the product were 103.3°C and 152.8°C (Figure 54). TGA showed that the weight loss of the product at 100°C was about 3.2% (Figure 55). IC showed that the concentration of free base of the product was 0.5 mg / mL and that of sulfate ion was 162.5 mg / L, so the stoichiometric ratio of base:acid in the product was about 1:1.7, which is unreasonable. The amorphous sulfate salt (sample number: Y11526-15-RV3-methanol-acetonitrile) is chemically stable at the end of production, but is physically unstable due to its certain hygroscopicity, and is irrational in terms of the stoichiometric ratio of base:acid.

[0039] Example 13: 2 equivalents of amorphous p-toluenesulfonate (sample number: Y11526-23-FD11-water) Approximately 100 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask together with 2 equivalents of p-toluenesulfonic acid, 10 mL of 1,4-dioxane was added, and the mixture was reacted at 50° C. for 2 hours. The resulting clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then 1,4-dioxane was removed by freeze-drying to obtain a nearly amorphous substance. The resulting nearly amorphous substance was thoroughly dissolved in 10 mL of water, and the resulting clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then water was removed by freeze-drying to obtain 2 equivalents of amorphous p-toluenesulfonic acid salt. HPLC showed the product to be 99.6% pure. PLM showed the product to be a chunky sample (Figure 62). XRPD showed the product to be amorphous (Figure 58). DSC showed the product had a glass transition temperature of 98.4°C (Figure 59). TGA showed the product had a weight loss of about 3.8% at 140°C (Figure 60). 1H-NMR showed that the base:acid stoichiometry in the product was approximately 1:2 (Figure 61). Two equivalents of amorphous p-toluenesulfonate (sample number: Y11526-23-FD11-water) is chemically stable at the end of manufacture and has a reasonable base:acid stoichiometry, but is physically unstable as it quickly solidifies and coalesces into a glassy form upon brief exposure to environmental conditions (Figure 63).

[0040] Example 14: Amorphous sulfosalicylate (sample number: Y11526-25-FD13-1,4-dioxane) Approximately 100 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask together with 1 equivalent of sulfosalicylic acid, 10 mL of 1,4-dioxane was added, and the mixture was reacted at 50° C. for 2 hours. The resulting clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then 1,4-dioxane was removed by freeze-drying to obtain an amorphous sulfosalicylic acid salt. HPLC showed the product to be 99.7% pure. The product showed to be an irregular sample (Figure 68). XRPD showed the product to be amorphous (Figure 64). DSC showed the product had a glass transition temperature of 72.1°C (Figure 65). TGA showed the product had a weight loss of about 1.2% at 80°C (Figure 66). 1 H-NMR showed that the stoichiometry of base:acid in the product was about 1:0.8 (Figure 67), which is unreasonable. Amorphous sulfosalicylate (sample number: Y11526-25-FD13-1,4-dioxane) is chemically and physically stable at the end of its manufacturing process, but has an unreasonable base:acid stoichiometry.

[0041] Example 15: Amorphous sulfosalicylate (sample number: Y11526-25-FD12-1,4-dioxane) Approximately 100 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask together with 2 equivalents of sulfosalicylic acid, 10 mL of 1,4-dioxane was added, and the mixture was reacted at 50° C. for 2 hours. The resulting clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then 1,4-dioxane was removed by freeze-drying to obtain an amorphous sulfosalicylic acid salt. HPLC showed the product to be 99.8% pure. PLM showed the product to be an irregular sample (Figure 73). XRPD showed the product to be amorphous (Figure 69). DSC showed the product had a glass transition temperature of 86.3°C (Figure 70). TGA showed the product had a weight loss of about 2.7% at 110°C (Figure 71). 1 H-NMR showed that the stoichiometry of base:acid in the product was about 1:1.5 (Figure 72), which is unreasonable. Amorphous sulfosalicylate (sample number: Y11526-25-FD12-1,4-dioxane) is chemically and physically stable at the end of its manufacturing process, but has an unreasonable base:acid stoichiometry.

[0042] Example 16: Amorphous L-Malate (Sample Number: Y11526-17-RV6-Methanol-Dichloromethane) Approximately 100 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask with 1 equivalent of L-malic acid, and 10 mL of 1,4-dioxane was added and reacted for 2 hours at 50° C. The resulting clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, after which the 1,4-dioxane was removed by freeze-drying to obtain a highly crystalline material. Approximately 80 mg of the resulting highly crystalline material was placed in a 40 mL glass flask, and approximately 10 mL of methanol / dichloromethane (v:v=1:1) was added to obtain a clear solution, which was then subjected to high speed volatilization to remove the solvent, yielding amorphous L-malate. HPLC showed that the purity of the product was 91.1%, i.e., the purity of the salt obtained at the end of the preparation was clearly decreased compared to the purity of the free base of the salt before preparation. PLM showed that the product was an irregular sample (Figure 78). XRPD showed that the product was amorphous (Figure 74). DSC showed that the glass transition temperature of the product was 80.8°C (Figure 75). TGA showed that the weight loss of the product at 120°C was about 3.3% (Figure 76). 1 H-NMR showed that the stoichiometry of base:acid in the product was about 1:0.6 (Figure 77), which is unreasonable. The amorphous L-malate (sample number: Y11526-17-RV6-methanol-dichloromethane) is at least chemically unstable at the end of the manufacturing process and has an unreasonable base:acid stoichiometry.

[0043] Example 17: 1 equivalent of amorphous citrate salt (sample number: Y11526-10-FD6-1,4-dioxane) Approximately 100 mg of the compound of formula (I) (purity 99.9%) was weighed out and mixed with 1 equivalent of citric acid. The mixture was placed in a 40 mL glass flask, 10 mL of 1,4-dioxane was added, and the mixture was allowed to react for 2 hours at 50° C. The resulting clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, and then 1,4-dioxane was removed by freeze-drying to obtain 1 equivalent of amorphous citrate. HPLC showed that the purity of the product was 94.4%, i.e., the purity of the salt obtained at the end of the preparation was clearly decreased compared to the purity of the free base of the salt before preparation. PLM showed that the product was an irregular sample (Figure 83). XRPD showed that the product was amorphous (Figure 79). DSC showed that the product had no glass transition temperature (Figure 80). TGA showed that the product had a weight loss of about 9.6% at 120°C (Figure 81). 1 H-NMR showed that the base:acid stoichiometry in the product was approximately 1:1 (Figure 82). One equivalent of amorphous citrate (sample number: Y11526-10-FD6-1,4-dioxane) is at least chemically unstable, although at the end of the preparation, the base:acid stoichiometry is reasonable.

[0044] Example 18: 1 equivalent of amorphous L-tartrate salt (sample number: Y11526-10-FD7-1,4-dioxane) Approximately 100 mg of the compound of formula (I) (purity 99.9%) was weighed out and placed in a 40 mL glass flask together with 1 equivalent of L-tartaric acid, and 10 mL of 1,4-dioxane was added and reacted for 2 hours at 50° C. The resulting clear solution was pre-frozen in a dry ice / ethanol mixture for 2 hours, after which 1,4-dioxane was removed by freeze-drying to obtain 1 equivalent of amorphous L-tartrate. HPLC showed that the product had decomposed (Figure 88). XRPD showed that the product was amorphous (Figure 84). DSC showed that the product had no glass transition temperature (Figure 85). TGA showed that the product had a weight loss of about 8.7% at 120°C (Figure 86). 1 H-NMR showed that the base:acid stoichiometry in the product was approximately 1:1 (Figure 87). One equivalent of amorphous L-tartrate (sample number: Y11526-10-FD7-1,4-dioxane) is at least chemically unstable, although at the end of the preparation, the stoichiometric ratio of base:acid is reasonable.

[0045] As can be seen from Examples 1 to 18, When the molar ratio of base to acid is 1:1, sulfosalicylic acid and L-malic acid cannot make the resulting salt have a stoichiometric ratio of the compound of formula (I):acid=1:1; When the molar ratio of base to acid is 1:1, hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, ethanesulfonic acid, maleic acid, hydrobromic acid, citric acid and L-tartaric acid can provide the resulting salt with a stoichiometric ratio of the compound of formula (I):acid=1:1; When the molar ratio of base to acid is 1:2, nitric acid, sulfuric acid, and sulfosalicylic acid cannot make the resulting salt have a stoichiometric ratio of the compound of formula (I):acid=1:2; and When the molar ratio of base to acid is 1:2, hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid can provide a stoichiometric ratio of the compound of formula (I):acid=1:2 in the resulting salt.

[0046] As can be seen from Examples 1 to 18, One equivalent of amorphous citrate, one equivalent of amorphous L-tartrate, amorphous nitrate and amorphous L-malate are chemically unstable at the end of the manufacturing process. The two equivalents of amorphous p-toluenesulfonate and amorphous sulfate are physically unstable at the end of the preparation process; and 1 equivalent of amorphous hydrochloride, 2 equivalents of amorphous hydrochloride, 1 equivalent of amorphous methanesulfonate, 2 equivalents of amorphous methanesulfonate, 1 equivalent of amorphous benzenesulfonate, 2 equivalents of amorphous The crystalline benzenesulfonate, one equivalent of the amorphous ethanesulfonate, one equivalent of the amorphous maleate, one equivalent of the crystalline hydrobromide and the amorphous sulfosalicylate are chemically and physically stable at the end of manufacture.

[0047] Example 19: Solid Storage Safety Test Various amorphous solid salts were weighed out (2 portions of 2 mg samples were weighed out for use in solid storage safety studies, followed by purity measurement, and 1 portion of 10 mg samples was weighed out for use in solid storage safety studies, followed by XRPD measurement), and placed in a glass flask. In the solid storage safety test at 25°C / 60%RH, the amorphous solid salts were left open in a constant temperature and humidity box at 25°C / 60%RH, and left for one week away from light (i.e., "solid / 25°C / 60%RH / open / one week"); in the solid storage safety test at 60°C, the amorphous solid salts were left closed in a 60°C oven, and heated for one week away from light (i.e., "solid / 60°C / closed container / one week"); then, the samples were taken out and purity measurement, crystal form detection, and appearance observation were performed, respectively. The above-mentioned solid storage safety test was carried out for Examples 1 to 10, and the results are shown in Table 1.

[0048] [Table 8]

[0049] The amorphous free base exhibited good physical and chemical stability under the storage safety test conditions of "solid / 25°C / 60% RH / open / 1 week" and changed from amorphous to moderately crystalline under the storage safety test conditions of "solid / 60°C / closed container / 1 week".

[0050] One equivalent of the amorphous hydrochloride salt exhibited good physical and chemical stability under the storage safety test conditions of "solid / 25°C / 60% RH / open / 1 week", and purity loss occurred (approximately 2%) under the storage safety test conditions of "solid / 60°C / closed container / 1 week".

[0051] The 2 equivalents of amorphous hydrochloride salt showed slight discoloration and some hygroscopicity (partial aggregation) under the storage safety test conditions of "solid / 25°C / 60% RH / open / 1 week" and good physical and chemical stability under the storage safety test conditions of "solid / 60°C / closed container / 1 week".

[0052] One equivalent of the amorphous methanesulfonate salt showed good physical and chemical stability under both of the two storage safety test conditions: "solid / 25°C / 60% RH / open / 1 week" and "solid / 60°C / closed container / 1 week."

[0053] Two equivalents of the amorphous methanesulfonate salt changed from amorphous to low crystallinity under the storage safety test conditions of "solid / 25°C / 60% RH / open / 1 week" and showed a certain degree of hygroscopicity (aggregation) under the storage safety test conditions of "solid / 60°C / closed container / 1 week" and showed a certain degree of hygroscopicity (partial aggregation).

[0054] One equivalent of amorphous benzenesulfonate salt underwent purity loss (approximately 2%) under storage safety test conditions of "solid / 25°C / 60% RH / open / 1 week", but showed good physical and chemical stability under storage safety test conditions of "solid / 60°C / closed container / 1 week".

[0055] The 2-equivalent amorphous benzenesulfonate salt showed slight discoloration and obvious hygroscopicity (solidified and fused to a glass-like state) under the storage safety test conditions of "solid / 25°C / 60% RH / open / 1 week", but showed good physical and chemical stability under the storage safety test conditions of "solid / 60°C / sealed container / 1 week".

[0056] One equivalent of the amorphous ethanesulfonate salt exhibited obvious hygroscopicity (solidified and fused to a glass-like state) under the storage safety test conditions of "solid / 25°C / 60% RH / open / 1 week" and good physical and chemical stability under the storage safety test conditions of "solid / 60°C / closed container / 1 week".

[0057] One equivalent of amorphous maleate salt under the storage safety test conditions of "solid / 25°C / 60% RH / open / 1 week" showed slight discoloration and a certain degree of hygroscopicity (aggregation), and under the storage safety test conditions of "solid / 60°C / closed container / 1 week" a purity loss occurred (approximately 2%) and the amorphous transformation changed to low crystallinity.

[0058] One equivalent of the crystalline hydrobromide salt showed good physical and chemical stability under both storage safety test conditions: solid / 25°C / 60% RH / open / 1 week and solid / 60°C / closed container / 1 week.

[0059] As can be seen from Example 19, One equivalent of amorphous benzenesulfonate, one equivalent of amorphous hydrochloride, and one equivalent of amorphous maleate are chemically unstable under the storage conditions of "solid / 25°C / 60%RH / open / 1 week" and / or "solid / 60°C / closed container / 1 week". 2 equivalents of the amorphous hydrochloride salt, 2 equivalents of the amorphous methanesulfonate salt, 2 equivalents of the amorphous benzenesulfonate salt, 1 equivalent of the amorphous ethanesulfonate salt, and 1 equivalent of the amorphous maleate salt are physically unstable under the storage conditions of "solid / 25°C / 60% RH / open / 1 week" and / or "solid / 60°C / closed container / 1 week"; and One equivalent of the amorphous methanesulfonate salt and one equivalent of the crystalline hydrobromide salt are chemically and physically stable under the storage conditions of "solid / 25°C / 60% RH / open / 1 week" and "solid / 60°C / closed container / 1 week."

[0060] Example 20: Solid solubility test Five parts of each amorphous solid salt (corresponding to 20 mg of free base) were weighed out and added to 10 mL or less of each solvent (0.1 N HCl solution (pH 1.0), 50 mM phosphate buffer (pH 4.5), FeSSIF-V1 (pH 5.0), FaSSIF-V1 (pH 6.5) and SGF (pH 2.0)) and stirred at 37°C for 2 hours. The suspensions were then centrifuged at 37°C and the solubility of the supernatants was measured by HPLC and the XRPD of the solid fraction was measured. The target solubility was at least 2 mg (of free base) / mL.

[0061] The above 2-hour solid solubility test was carried out for Examples 1 to 10, and the results are shown in Table 2. Similarly, the 24-hour solid solubility test was carried out for Examples 1 and 4, and the results are shown in Table 3.

[0062] [Table 9] [Table 10] [Table 11]

[0063] In a 2-hour solid solubility test, 2 equivalents of amorphous benzenesulfonate did not meet the solubility of 2 mg / mL in 0.1N HCl solution (pH 1.0), and 1 equivalent of crystalline hydrobromide did not meet the solubility of 2 mg / mL in FaSSIF-V1 (pH 6.5), while 1 equivalent of amorphous hydrochloride, 2 equivalents of amorphous hydrochloride, 1 equivalent of amorphous methanesulfonate, 2 equivalents of amorphous methanesulfonate, 1 equivalent of amorphous benzenesulfonate, 1 equivalent of amorphous ethanesulfonate, and 1 equivalent of amorphous maleate all had solubilities greater than 2 mg / mL in all test solvents. In addition, in a 24-hour solid solubility test, the amorphous free base and 1 equivalent of amorphous methanesulfonate had solubilities greater than 2 mg / mL in FeSSIF-V1 (pH 5.0) and FaSSIF-V1 (pH 6.5).

[0064] As can be seen from Examples 1 to 20, one equivalent of the amorphous methanesulfonate simultaneously has a reasonable salt-forming equivalent ratio, better chemical stability, better physical stability, and better solubility.

[0065] Although the above invention has been described in some detail by way of illustration and example for purposes of clarity of understanding, it will be understood that the scope of the present invention is not limited to these descriptions and examples.

Claims

1. A salt formed by a compound of formula (I) below and an acid: 【Chemistry 1】 [The acid is selected from hydrochloric acid, methanesulfonic acid, benzenesulfonic acid, ethanesulfonic acid, maleic acid and hydrobromic acid.]

2. The salt of claim 1, wherein the acid is selected from hydrochloric acid, methanesulfonic acid and maleic acid.

3. 3. The salt according to claim 1 or 2, wherein the equivalent ratio of the compound of formula (I) to the acid is 1:1 or 1:

2.

4. The salt of claim 3, wherein the acid is methanesulfonic acid.

5. 5. The salt according to claim 4, wherein the equivalent ratio of the compound of formula (I) to the acid is 1:

1.

6. A pharmaceutical composition comprising the salt according to any one of claims 1 to 5 and a pharma- ceutically acceptable carrier.

7. Use of the salt according to any one of claims 1 to 5 in the manufacture of a medicament for treating EGFR exon 20 insertion mutant non-small cell lung cancer (NSCLC).

Citation Information

Patent Citations

  • Pyrimidine or triazine derivative, and preparation method and use thereof

    CN105461695A

  • Triazine derivative for treating cancer

    CN106928200A

  • Heteroaryl compounds for kinase inhibition

    JP2018012712A

  • EGFR inhibitor compounds

    JP2019516766A

  • Triazine compound and pharmaceutically acceptable salt thereof

    WO2018210246A1